(untitled) (Altre Modernità, 2012)
Bachelard displays throughout his epistemological and esthetical work a particular anthropology. However this anthropology has never been systemically structured in a book but has been only fragmented in his analyses on the formation and transformation of concepts and images. The bachelardian man has a complex nature that mobilises every dimension of the subject: his body and his mind but also his affectivity, his will and his imagination. It is this image of an integral man that we will try to appropriate in this paper.